Empowering Teachers Through Digital Assessment: Enhancing Competence and Efficiency with Google Forms in Primary Education - Ahmad Fauzan; A. Sa’dullah (Communautaire: Journal of Community Service, 2024)
This study focuses on analyzing the effectiveness of training on the use of Google Form as an online exam medium in improving teacher competence and the efficiency of the assessment process at SD Negeri Besuk Agung, Probolinggo. The main objective of this study is to identify how this training can improve teachers' skills in using digital technology, as well as its impact on student motivation and participation. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, participatory observations, and document analysis. The results of the study show that Google Form training significantly increases teachers' confidence and competence in using this technology, as well as speeds up the assessment process. However, challenges such as limited infrastructure and access to technology among students still need to be overcome. The implications of this study emphasize the importance of infrastructure support and ongoing training to maximize the benefits of technology in education. This research makes an important contribution to the basic education literature and offers practical guidance for technology adoption in resource-constrained schools.